SERUM AND ESTRUS MUCUS ENZYMES ACTIVITIES AND CHEMISTRY OF NORMAL AND REPEAT BREEDER FRIESIAN CATTLE - KADOOM, A K; EL-HENAWY, M A A (The Indian Journal of Animal Reproduction, 2022)
Estrus mucus (EM) and blood (serum) was collected from 40 apparently normal cattle (Normal breeder, NB= 20; Repeat breeder, RB = 20) at the time of insemination for glucose, minerals, alkaline phosphatase (ALP),lactic dehydrogenase (LDH) and α-amylase concentration. In NB cattle, serum glucose and magnesium werelow (p
Keywords: Blood serum; Enzyme; Estrus mucus; Fertility; Mineral